2023
DOI: 10.1097/prs.0000000000011021
|View full text |Cite
|
Sign up to set email alerts
|

Free Flap Reconstruction in the Era of Commercial Price Transparency – What are We Paying For?

Danielle H. Rochlin,
Nada M. Rizk,
Babak Mehrara
et al.

Abstract: Background: Commercial rates for free flap reconstruction were not known publicly prior to the 2021 Hospital Price Transparency Final Rule. The purpose of this study was to examine commercial facility payments to characterize nationwide variation for microsurgical operations and identify opportunities to improve market effectiveness. Methods: A cross-sectional study was performed using 2022 commercial insurance pricing merged with hospital performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…4 17 18 19 20 The difficulty in navigating our health system whether insured or otherwise is demonstrated with the enactment of the Hospital Price Transparency Rule in 2021, where analysis of breast reconstruction pricing has suggested that privately insured patients are paying markedly different prices for breast reconstruction depending on insurer, plan, and hospital. 21 This systemic complexity both obscures patient interpretation of costs and creates barriers to providers in counseling their patients.…”
Section: Discussionmentioning
confidence: 99%
“…4 17 18 19 20 The difficulty in navigating our health system whether insured or otherwise is demonstrated with the enactment of the Hospital Price Transparency Rule in 2021, where analysis of breast reconstruction pricing has suggested that privately insured patients are paying markedly different prices for breast reconstruction depending on insurer, plan, and hospital. 21 This systemic complexity both obscures patient interpretation of costs and creates barriers to providers in counseling their patients.…”
Section: Discussionmentioning
confidence: 99%
“…In this article, the authors leverage data made available through the Hospital Transparency Rule to analyze rates for microsurgical free flaps negotiated between hospitals and insurance companies. 1 Specifically, the authors explore 20,528 commercial rates across 675 hospitals for nine microsurgical free flaps based on CPT code. The key findings of this study are that rates vary widely between hospitals; are higher in more concentrated (less competitive) markets; are lower in safety net and teaching hospitals; and have an inconsistent correlation with value, outcomes, and equity.…”
Section: Wwwprsjournalcommentioning
confidence: 99%